Genotype and rhizobium inoculation modulate the assembly of soybean rhizobacterial communities. (20th February 2019) - Zhong, Yongjia; Yang, Yongqing; Liu, Peng; Xu, Ruineng; Rensing, Christopher; Fu, Xiangdong; Liao, Hong
Abstract: Rhizosphere bacterial communities are vital for plants, yet the composition of rhizobacterial communities and the complex interactions between roots and microbiota, or between microbiota, are largely unknown. In this study, we investigated the structure and composition of rhizobacterial communities in two soybean cultivars and their recombinant inbred lines contrasting in nodulation through 16S rRNA amplicon sequencing in two years of field trials. Our results demonstrate that soybean plants are able to select microbes from bulk soils at the taxonomic and functional level. Soybean genotype significantly influenced the structure of rhizobacterial communities and resulted in dramatically different co‐occurrence networks of rhizobacterial communities between different genotypes of soybean plants. Furthermore, the introduction of exogenous rhizobia through inoculation altered soybean rhizobacterial communities in genotype‐dependent manner. Rhizobium inoculation not only stimulated the proliferation of potential beneficial microbes but also increased connections in rhizobacterial networks and changed the hub microbes, all of which led to the association of distinctive bacterial communities. Taken together, we demonstrated that the assembly of soybean rhizobacterial communities was determined by both genotype and the introduction of exogenous rhizobia. These findings bolster the feasibility of root microbiome engineering through inoculation of specific microbial constituents. Abstract : Rhizosphere bacterial communities are vital for plant growth and development. In this study, we demonstrate that soybean plants display taxonomic and functional selection on microbes from bulk soils. Besides, both soybean genotype and exogenous rhizobia through inoculation significantly influence the structure of rhizobacterial communities. These findings bolster the feasibility of root microbiome engineering through inoculation of specific microbial constituents.